\((x^2-y^2), (x^2y-xy^2), (x+y)\) এর চতুর্থ সমানুপাতী নির্ণয় করো ।
Madhyamik 2010
ধরি, \((x^2-y^2), (x^2y-xy^2), (x+y)\) এর চতুর্থ সমানুপাতী \(p\)
\(\therefore \cfrac{(x^2-y^2)}{(x^2y-xy^2)}=\cfrac{(x+y)}{p}\)
বা, \(p(x^2-y^2)=(x+y)(x^2y-xy^2)\)
বা, \(p=\cfrac{(x+y)(x^2y-xy^2)}{(x^2-y^2)}\)
বা, \(p=\cfrac{(x+y)\times xy(x-y)}{(x+y)(x-y)}\)
বা, \(p=\cfrac{\cancel{(x+y)}\times xy\cancel{(x-y)}}{\cancel{(x+y)}\cancel{(x-y)}}\)
বা, \(p=xy\)
\(\therefore (x^2-y^2), (x^2y-xy^2), (x+y)\) এর চতুর্থ সমানুপাতী হল \(xy\)